2014
DOI: 10.1002/zaac.201400335
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Superstructure, and Vacancy‐Ordering in 2H‐CuxTa1+ySe2 (x, y = 0.52, 0 and 0.16, 0.08)

Abstract: Abstract. Single crystals of Cu x Ta 1+y Se 2 were grown by chemical vapor transport. Single crystals of different compositions were obtained at slightly different reaction conditions from mixtures of the reactants of the same nominal composition. It is suggested that different diameters of the ampoules imply different contributions of convection and diffusion to the mass transport, and thus are responsible for different ratios of the amount of Cu, Ta, and Se transported. 2H-Cu 0.52 TaSe 2 (x = 0.52, y = 0) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Interestingly, information about doping 1T-TaS 2 with coinage metals is missing. Typically, copper and silver form donor intercalation compounds with TaS 2 , where copper and silver are located rather in the van der Waals gaps than substituting tantalum within the TaS 2 -sheets [29][30][31]. During our research on copper tantalum sulfides, we found that a sufficiently high amount of sulfur excess can force copper to substitute tantalum in 1T-TaS 2 .…”
Section: Introductionmentioning
confidence: 79%
“…Interestingly, information about doping 1T-TaS 2 with coinage metals is missing. Typically, copper and silver form donor intercalation compounds with TaS 2 , where copper and silver are located rather in the van der Waals gaps than substituting tantalum within the TaS 2 -sheets [29][30][31]. During our research on copper tantalum sulfides, we found that a sufficiently high amount of sulfur excess can force copper to substitute tantalum in 1T-TaS 2 .…”
Section: Introductionmentioning
confidence: 79%
“…Several studies have been reported up to now on nonstoichiometric compounds based on Ni and chalcogens owing to the partial occupancy of metal ions. The investigation of fundamental relations between the structures of compounds and their distinct properties is of utmost importance. Multiscale computation methods and their applications in lithium ion batteries (LIBs) by use of different atomic-scale simulations and macroscale simulations have been studied before. , The study can not only minimize the experimental and theoretical gaps but also predict path-independent properties to understand its performance.…”
Section: Introductionmentioning
confidence: 99%
“…The weak interlayer bonding permits intercalations, quite akin to other layered materials such as graphite, allowing the incorporation of various metal atoms and organic molecules , between the layers to form stoichiometric or nonstoichiometric compounds. Depending on the intercalated species, changes in the physical properties of the host can occur.…”
Section: Introductionmentioning
confidence: 99%